2014
DOI: 10.1186/1477-7827-12-41
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous antral follicle formation and metaphase II oocyte from a non-stimulated prepubertal ovarian tissue xenotransplant

Abstract: BackgroundCurrent strategies in cancer treatment have markedly increased the rates of remission and survival for cancer patients, but are often associated with subsequent sterility. While there are various options available to an adult female depending on the patient’s particular situation, the only realistic option for preserving fertility in prepubertal females is to cryopreserve ovarian tissue. This is the first report of a morphologically mature oocyte collected from non-stimulated prepubertal ovarian tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…No cases have been reported of pregnancy after ovarian tissue cryopreservation in childhood or adolescence. However, findings from a recent study in an ovine model 28 have shown that grafting immature ovarian tissue can restore spontaneous puberty and fertility, 28 and a mature oocyte at metaphase II has been derived from a prepubertal ovarian biopsy sample xenografted into a mouse 29 . In our study population, none of the young women has yet requested use of their stored tissue, nor are we aware of such use for fertility elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…No cases have been reported of pregnancy after ovarian tissue cryopreservation in childhood or adolescence. However, findings from a recent study in an ovine model 28 have shown that grafting immature ovarian tissue can restore spontaneous puberty and fertility, 28 and a mature oocyte at metaphase II has been derived from a prepubertal ovarian biopsy sample xenografted into a mouse 29 . In our study population, none of the young women has yet requested use of their stored tissue, nor are we aware of such use for fertility elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Finally, an in vivo system that is used to evaluate tissue quality is xenotransplantation, in which small pieces of human ovarian tissue are transplanted into a host species (typically immunocompromised mice) and follicle development, endocrine function, and mature gamete production are monitored over a period of months. 44,45 Although these assays can provide important information about how specific conditions affect ovarian tissue function, they can be time-consuming, costly, and inefficient or impractical for application with human material. Moreover, the results from these assays may not be representative or predictive of the quality of the tissue as a whole.…”
Section: Figmentioning
confidence: 99%
“…We could demonstrate that a maturing oocyte can be obtained from prepubertal human ovarian tissue; achieved via xenotransplantation in oophorectomized severe combined immunodeficiency (SCID) mice without any exogenous hormone stimulation 17 . Our following aim was to investigate if spontaneous antral follicle formation as well as oocyte maturation would occur again from the same xenograft, still without administering any hormones.…”
Section: Introductionmentioning
confidence: 99%